Long-term ecological trajectories of a disturbed Mediterranean coastal lagoon (Biguglia lagoon): Ecosystem-based approach and considering its resilience for conservation? - Ligorini, Viviana; Malet, Nathalie; Garrido, Marie; Four, Brian; Etourneau, Sabrina; Leoncini, Antoine Simon; Dufresne, Christiane; Cecchi, Philippe; Pasqualini, Vanina (Frontiers in Marine Science, 2022)
Coastal lagoons are subjected to ever-increasing direct or indirect anthropic pressures and are inexorably deteriorating with serious issues regarding their resilience. In this paper, we assessed the functioning and evolution of the highly disturbed Biguglia coastal lagoon (Mediterranean Sea, Corsica) through an ecosystem-based approach (EBA), in using multiple biotic and abiotic proxies (hydro-climatic context, eutrophication), considering its connectivity to sea and watershed and biological compartments (macrophytes, phytoplankton, invasive species), and taking into account human influence (management actions, fishing activities). The aim of this work is firstly to provide a comprehensive analysis of its long-term (2000-2021) ecological evolution trajectory. Then, based on these results, to anticipate management strategies for supporting its conservation and restoration, and the maintenance of ecosystem services it offers. Results revealed that while the lagoon showed to these days a good capacity to recover after disturbance and absorb change, it recently exhibited considerable changes in its phytoplankton community composition, developed an increased susceptibility to biological invasion, and experimented a drastic reduction of its fish stocks. The major interannual variations of the mean salinity, strongly dependent on management interventions beyond natural climatic variability, summarized this instability. In the future, the lagoon may no longer be able to cope with even small disturbances, which could then be sufficient to reach a breakpoint and tip the system permanently into undesired/degraded states. We demonstrated that local and punctual management actions are not always beneficial for the entire ecosystem, or even detrimental in some instances. Such a retrospective ecosystem-based approach is fundamental for producing the holistic insights required to implement efficient integrated ecosystem management. This further helps enhancing lagoon resilience and hence preserve its ecosystem services in the context of increasing global changes. Such lessons are useful anywhere for comparable ecosystems.